2009
DOI: 10.1088/0022-3727/42/15/155208
|View full text |Cite
|
Sign up to set email alerts
|

A novel method to determine the electron temperature and density from the absolute intensity of line and continuum emission: application to atmospheric microwave induced Ar plasmas

Abstract: An absolute intensity measurement (AIM) technique is presented that combines the absolute measurements of the line and the continuum emitted by strongly ionizing argon plasmas. AIM is an iterative combination of the absolute line intensity–collisional radiative model (ALI–CRM) and the absolute continuum intensity (ACI) method. The basis of ALI–CRM is that the excitation temperature T13 determined by the method of ALI is transformed into the electron temperature Te using a CRM. This gives Te as a weak function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 34 publications
1
35
0
Order By: Relevance
“…It was found that at the position of 1 mm behind the tube exit, where the measurements takes place, the pure Ar plasma does not change substantially if the power and flow rate are changed moderately. A feature that was already observed in [24] for the pure argon TIA. On the other hand, the plasmas in Ar-H 2 mixtures are sensitive to changes in the power.…”
Section: Atmospheric Surfatron Setupsupporting
confidence: 67%
See 2 more Smart Citations
“…It was found that at the position of 1 mm behind the tube exit, where the measurements takes place, the pure Ar plasma does not change substantially if the power and flow rate are changed moderately. A feature that was already observed in [24] for the pure argon TIA. On the other hand, the plasmas in Ar-H 2 mixtures are sensitive to changes in the power.…”
Section: Atmospheric Surfatron Setupsupporting
confidence: 67%
“…The ALI method is based on the bottom part of ASDF of argon [24]. By including the ASDF-top it is possible to obtain several "excitation temperatures" of the distribution.…”
Section: Electron Temperature Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…96 With regard to the articles cited, they can be divided into broad categories dealing with population distributions and deviations from equilibrium, [97][98][99][100][101][102][103][104][105][106][107][108][109][110] classification of diagnostic methods, 111,112 local and space-integrated intensity definitions, 113,114 ion-toneutral ratios and their diagnostic relevance, [115][116][117][118][119][120][121][122][123][124][125] line-to-continuum ratios, [126][127][128][129][130][131] scattering methods, [132][133][134][135] evaluation of electron number density and plasma temperature, including Stark broadening of H-lines, Stark broadening of non-hydrogenic transitions, influence of the instrumental profile, [199][200][201][202][203][204] calibration of...…”
Section: Local Thermodynamic Equilibrium Theoretical Equilibrium Expmentioning
confidence: 99%
“…The ground-state density compared to the density of the excited radiating species gives the electron temperature by employing a collisional radiative model [7]. The measurement of the continuum of atomic plasmas can give the electron density [8,9]. In the case that the degree of ionization is small, the atoms are the main scatter partners of the electrons so that again the n a value is needed for a correct interpretation of the continuum spectrum.…”
Section: Introductionmentioning
confidence: 99%